Does Batman™ affect EF because he is benevolent or skilful? The effect of different pretend roles on pre-schoolers' executive functions. Issue 10 (27th July 2021) - Veraksa, Alexander Nikolaevich; Gavrilova, Margarita Nikolaevna; Bukhalenkova, Daria Аlexeevna; Almazova, Olga; Veraksa, Nickolay Evgenievich; Colliver, Yeshe
ABSTRACT: Previous research has indicated that young children's executive functions (EFs) can be bolstered through role-play [e.g. the 'Batman ™ effect'; White et al.]. However, what is not clear is whether it is the role-playing of another's perspective, or something about the role played, which is responsible for the Batman ™ effect. The current experiment investigated the effects of role-play of different roles (protagonist, villain, and sage) with different traits (benevolence, malevolence, skill) on 80 five- to six-year-old children's EF performance. Results indicated significantly improved cold – but not hot – EF scores for the Sage and Control groups. Consistent with Vygotsky's theory that children transfer imagined content into real-world applications, this study provides preliminary evidence that pretending to be someone with EF skills can bolster young children's cold EF performance.